PPREFERENSI KONSUMEN TERHADAP PRODUK TANAMAN HIAS TANUKI BONSAI - Sa'diyah, Ana Arifatus; Dimin, Dimin; Nurhananto, Dwi Asnawi (Agrinesia: Jurnal Ilmiah Agribisnis, 2024)
Tanuki Bonsai is a plant that has prospects for development. The aim of the research is to analyze consumer preferences, analyze the order of attributes of tanuki bonsai ornamental plants based on the level of importance according to consumer preferences, and find out the recommendations for the most influential attributes according to consumer preferences at Tanimeja PT. Graha Mitratama Innovation Malang City. The research is located at Tanimeja PT. Graha Mitratama Innovation Malang City. The research uses conjoint analysis methods, validity and reliability tests and descriptive analysis methods. The results of the analysis show that the order of tanuki bonsai attributes is based on the level of importance according to consumers, from the most important first, namely the price attribute with three statements with a relative importance value of 32.910%, second place is pot size with three statements with a relative importance value of 30.526%, third place is wood. dead with two statements with a relative importance value of 18.397%, the fourth is a type of plant with two statements with a relative importance value of 18.168%. Based on recommendations from research analysis data, it was obtained that the first most influential attribute was price, second was pot size, third was dead wood, and fourth was plant type. The results of the research provide implications for attention to the price attribute of Tanuki Bonsai, considering that price is the most important attribute.